Greenland, icebergs at Kejser Franz Joseph Fjord - Boyd, Louise Arner, 1887-1972 (1931)
July 29, 1931. Kaiser Franz Josef Fjord [Kejser Franz Joseph Fjord]. Inner end. On left; Riddarborgen (Peak) at S.W. entrance to Kjerulfs [Kjerulf] Fjord. In background; mountains above Nordenskjold Glacier [Nordenskiöld Gletscher]. On right; north side of Kaiser Franz Josef Fjord [Kejser Franz Joseph Fjord], opposite Riddarborgen. Photo taken from bridge of S.S. Veslekari.